2020
DOI: 10.1177/0961000620949653
|View full text |Cite
|
Sign up to set email alerts
|

Understanding fake news during the Covid-19 health crisis from the perspective of information behaviour: The case of Spain

Abstract: The health crisis brought about by Covid-19 has generated a heightened need for information as a response to a situation of uncertainty and high emotional load, in which fake news and other informative content have grown dramatically. The aim of this work is to delve into the understanding of fake news from the perspective of information behaviour by analysing a sample of fake news items that were spread in Spain during the Covid-19 health crisis. A sample of 242 fake news items was collected from the Maldita.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 48 publications
0
18
0
6
Order By: Relevance
“…Our poor knowledge of the virus has favored the development of false news. Indeed, without any empirical research on the subject, newspapers and governments spread information that could contradict each other (Montesi 2020). The World Health Organization (WHO 2020) has emphasized that unverified news and misinformation that spreads rapidly through social media poses a serious threat to the COVID-19 response.…”
Section: Introductionmentioning
confidence: 99%
“…Our poor knowledge of the virus has favored the development of false news. Indeed, without any empirical research on the subject, newspapers and governments spread information that could contradict each other (Montesi 2020). The World Health Organization (WHO 2020) has emphasized that unverified news and misinformation that spreads rapidly through social media poses a serious threat to the COVID-19 response.…”
Section: Introductionmentioning
confidence: 99%
“…Banaji (Banaji, Bhat, 2019) found that peer-to-peer messaging services, file-sharing sites and in various cases the cross-platform app WhatsApp, have played a pivotal role in the lynching and other utmost violence resulting from the prevalence of false news in the state of India. They urged that messaging services and WhatsApp must be liable for stopping future crimes of this kind (Montesi, 2020). Moreover, the report argued about the proofs from the analysis of the messages forwarded by consumers and the consumers' justifications of and encouragement for passing on data that results out to be incorrect; in this way, while we locate that however the media and communication technologies' role has been overestimated and the other major roles i.e.…”
Section: Discussionmentioning
confidence: 84%
“…Fake news that are spread during crucial times, such as the COVID-19 pandemic, diminishes the idea of rational sharing, which in turn creates misinformation and disinformation. There is moral and intangible harm which makes readers get a hazy understanding on the actual details of the situation (Montesi, 2020). This is also reflected in several participants' point of view of the experiences falling prey to unauthenticated publications posted on social media platforms, especially when the situation persists and a lot of attention is being put on the subject matter.…”
Section: Discussionmentioning
confidence: 99%